Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Kelas X SMA/MA Pada Materi Pokok Protista Berbasis Pendekatan Ilmiah - Istikharah, Ria; Simatupang, Zulkifli (Universitas Negeri Medan, 2017)
This study aims to develop a LKPD based biological scientific approach on the subject matter of protista. The research design used is development research. A test target in this research is the grade X SMAN 4 Medan years lessons 2016/2017. Data collection was done by instrument in the form of questionnaire. File analysis using quantitative and qualitative descriptive analysis. The development of LKPD based biology scientific approach is done by using 3D model with stage define, design and develop. The results showed that the development of a scientific approach based LKPD based on expert assessment of the material obtained a score of 93% and the valuation expert learning obtained a score of 82% each with excellent category, while a small group of trial results obtained a score of 95% with the criteria very well. LKPD biology subject matter protists-based scientific approach that developed obtained the criteria very well and has fulfilled the requirements of eligibility for use as a medium of learning biology.